PENGEMBANGAN MEDIA KOMIK DIGITAL UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA KELAS IV SDN NGALIYAN 05 - Liza Natalia; Susilo Tri Widodo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to produce digital comic learning media to improve learning outcomes for class IV Pancasila Education at SDN Ngaliyan 05. The researcher used the Research and Development type of research with the model used by the researcher, namely the ADDIE development model. The subjects in this research were fourth-grade students at SDN Ngaliyan 05. Data collection techniques in this research were observation, interviews, questionnaires, and tests. Based on the results of the two validators, media experts obtained an average score of 93.75%, and material experts with an average score of 89.58%. By stating that the average result from the two validators is 91.66%, it states that digital comic media is in the very valid category. Meanwhile, the results of the practicality and effectiveness analysis that have been carried out show that the results of the practicality analysis for teachers and students obtained an average score of 98.38%. The N-Gain test obtained a value of 0.6958 with a medium classification, which means that digital comic media is effective. Based on research that has been carried out, it is stated that the digital comic learning media was found to be very valid, very practical, and effective in learning Pancasila education for class IV students at SDN Ngaliyan 05.